Association of novel triglyceride-glucose index-derived indices with hyperuricemia among oilfield workers - Liu, Haobiao; Li, Qingsong; Wali, Husna; Cai, Yingjie; Tang, Jing; Yang, Licheng; Yu, Xuefeng; Li, Jinsong; Yang, Bowei; Guo, Ziwei; Han, Jing; Du, Zhiyong (Frontiers in Nutrition, 2026)
ObjectivesThe association and predictive value of newer triglyceride-glucose (TyG)-derived anthropometric indices for hyperuricemia have not been systematically evaluated.MethodsLogistic regression, restricted cubic spline (RCS) modeling, subgroup analyses, and multiple sensitivity assessments were used to evaluate dose-response patterns and the robustness of findings. Discriminatory performance was further assessed using receiver operating characteristic curves.ResultsAll five TyG-derived indicators showed positive associations with hyperuricemia. Each one-standard deviation increase in triglyceride-glucose-a body shape index (TyG-ABSI), triglyceride-glucose-weight-adjusted waist index (TyG-WWI), triglyceride-glucose-conicity index (TyG-CI), triglyceride-glucose-body roundness index (TyG-BRI), and triglyceride-glucose-Chinese visceral adiposity index (TyG-CVAI) corresponded to 62, 45, 68, 82, and 88% higher odds, respectively. Similar trends appeared in categorical analyses, where the highest quartile exhibited markedly elevated risks compared with the lowest, ranging from 1.61-fold for TyG-WWI to 2.29-fold for TyG-CVAI. RCS analyses confirmed non-linear patterns, and subgroup findings across age, sex, and shift-work strata were largely consistent. Sensitivity analyses further supported the robustness of the results. Among all indicators, TyG-CVAI provided the greatest discriminative ability, with an AUC of 0.735 and statistically superior performance relative to the other indices.ConclusionTyG-derived anthropometric metrics, particularly TyG-CVAI, exhibit robust associations with hyperuricemia and demonstrate promising utility for metabolic risk stratification.